2020
DOI: 10.4049/immunohorizons.2000003
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deprivation in Human T Cells Induces Nonproliferating Accessory Helper Cells

Abstract: Iron uptake via the transferrin receptor (CD71) is a pivotal mechanism for T cell proliferation. Yet, it is incompletely understood if targeting of CD71 also affects the differentiation and functional polarization of primary human T cells. In this study, we demonstrate that inhibition of iron ingestion with blocking mAbs against CD71 induces nonproliferating T cells, which release high amounts of IL-2. Targeting of CD71 with blocking or nonblocking mAbs did not alter major signaling pathways and the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…3E). This is in accordance with previous reports by Berg et al, 21 who found that iron deprivation can cause growth arrest of T cells and restored upon addition of exogenous iron. Cortes et al 22 reported that ferritin up-regulation may support the survival of inflammatory cells in the microenvironment.…”
Section: Discussionsupporting
confidence: 94%
“…3E). This is in accordance with previous reports by Berg et al, 21 who found that iron deprivation can cause growth arrest of T cells and restored upon addition of exogenous iron. Cortes et al 22 reported that ferritin up-regulation may support the survival of inflammatory cells in the microenvironment.…”
Section: Discussionsupporting
confidence: 94%
“…Second, T cells produced more IL-2 and IL-10, suggesting that iron metabolism can be manipulated to control regulatory cytokine activity. In agreement with this, iron limitation in Jurkat T cells increased IL-2 secretion 45 . CD71 targeting was particularly beneficial to iTregs by increasing FoxP3 expression and suggests that they could have enhanced suppressive capacity.…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, defective iron uptake upon activation of our patient's T cells was associated with impaired activation, proliferation, mitochondrial metabolism, and cytokine-induced polarization. The reduction in CD25 and ICOS in TfR1 R22W patient's T cells suggests that late activation leading to proliferation was more signi cantly impaired due to TfR1 dysfunction [23]. Proven defective lymphocyte proliferation in TfR1 R22W patient cells was recovered with the exogenic iron con rming that the proliferation defect was due to iron de ciency.…”
Section: Discussionmentioning
confidence: 96%